2016
DOI: 10.1016/j.amsu.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Iliopsoas impingement after revision total hip arthroplasty treated with iliopsoas muscle transection

Abstract: IntroductionIliopsoas tendinitis after revision total hip arthroplasty (THA) is rare and its etiology and optimal treatment are still unclear. We report a case of iliopsoas impingement after revision THA with a Kerboull acetabular reinforcement device requiring two-level iliopsoas muscle transection.Presentation of caseA 70-year-old woman presented to our hospital complaining of debilitating right groin pain after revision THA with a Kerboull reinforcement device. She had undergone multiple hip operations afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…The present findings are supported by previous studies highlighting the importance of back problems, which worsen the results of THA and lead to poor results [12,13]. Periarticular pain is poorly described: the best described is iliopsoas impingement, because of its surgical treatment [14,15], but we found no studies of prevalence. Loosening is not the most common cause of painful THA, whereas it is the most common cause of revision; however, it represented only 10% of painful prostheses in the present series, so the other causes have to be borne in mind.…”
Section: Discussionsupporting
confidence: 89%
“…The present findings are supported by previous studies highlighting the importance of back problems, which worsen the results of THA and lead to poor results [12,13]. Periarticular pain is poorly described: the best described is iliopsoas impingement, because of its surgical treatment [14,15], but we found no studies of prevalence. Loosening is not the most common cause of painful THA, whereas it is the most common cause of revision; however, it represented only 10% of painful prostheses in the present series, so the other causes have to be borne in mind.…”
Section: Discussionsupporting
confidence: 89%
“…We concur with Morohashi et al. 9 that unexpected adhesions from the previous surgery may be encountered. When releasing the iliopsoas tendon at the lesser trochanter, metachronous proximal adhesions of the tendon may be present either to the proximal femoral at the level of the neck cut or to the anterior acetabular margin or to the anterior lip of the component itself.…”
Section: Discussionsupporting
confidence: 93%
“…A recent literature review found an overall success rate of 91.5% for surgical intervention at a mean of 22.7 months postoperatively [18, 19]. Compared to iliopsoas tenotomy, associated iliopsoas tenotomy and component revision presented similar functional outcomes but a higher rate of complications [18, 23, 25]. Single iliopsoas tenotomy could be appropriate for patients without radiographic evidences of the acetabular component malposition.…”
Section: Discussionmentioning
confidence: 99%